1997
DOI: 10.1099/00221287-143-5-1623
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenosomes of Metopus contortus physiologically resemble mitochondria

Abstract: The anaerobic free-living ciliated protozoon Metopus contortus is a grazer in anoxic marine sediments. It does not possess mitochondria, but it does have specialized organelles termed hydrogenosomes which release hydrogen gas. The cationic lipophilic cyanine dye DiOC,(3) is an indicator of transmembrane electrochemical potential. With the aid of confocal laser scanning microscopy (CLSM), the association of this dye with hydrogenosomes in situ was followed. Flow cytometric measurements showed that fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Rhodamine 123 has been used to stain mitochondria specifically in aerobically grown yeast (Lloyd et al, 1996), and it also accumulates in the hydrogenosomes of Trichomonas vaginalis (Harris, 2001). Similar specificity of uptake of the cationic cyanine dye dihexyloxacarbocyanine has been demonstrated in these hydrogenosomes (Humphreys et al, 1998), and its uptake has also been demonstrated in the free-living, ' anaerobic ' ciliate Metopus contortus (Biagini et al, 1997b). Our observations of structures with mitochondria-like functions in G. intestinalis further suggest the loss of fully fledged mitochondria from this parasite and the secondary nature of its amitochondrial status.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Rhodamine 123 has been used to stain mitochondria specifically in aerobically grown yeast (Lloyd et al, 1996), and it also accumulates in the hydrogenosomes of Trichomonas vaginalis (Harris, 2001). Similar specificity of uptake of the cationic cyanine dye dihexyloxacarbocyanine has been demonstrated in these hydrogenosomes (Humphreys et al, 1998), and its uptake has also been demonstrated in the free-living, ' anaerobic ' ciliate Metopus contortus (Biagini et al, 1997b). Our observations of structures with mitochondria-like functions in G. intestinalis further suggest the loss of fully fledged mitochondria from this parasite and the secondary nature of its amitochondrial status.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, it is suggested that their apparently deep-branching status is a consequence of more recent secondary evolutionary modifications of aerobic mitochondriate organisms. Hydrogenosomes, the redox-active organelles of the parabasalia (Mu$ ller, 1998 ;Humphreys et al, 1998), of anaerobic rumen ciliates (Embley et al, 1995) and chytrid fungi (Biagini et al, 1997d), and of some free-living ciliates living in anoxic sediments (Biagini et al, 1997b), are now also believed to have been derived from ancestral mitochondria (Biagini et al, 1997c ;Embley et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyruvate is central to this metabolism, and the relative rates of generation of the end-products are influenced by the ambient values for O # tension (Biagini et al, 1998 ;Paget et al, 1993a). Both of these organisms lack mitochondria or detectable cytochromes (Brugerolle, 1974 ;Paget et al, 1993b ;Biagini et al, 1997) (and hence oxidative phosphorylation), but do, however, have high affinities for O # , comparable to those of aerobic protozoa (Paget et al, 1993b ;Biagini et al, 1997). The consumption of O # has IP: 54.191.190.102 On: Fri, 11 May 2018 00:32:14 G. A. BIAGINI and OTHERS been shown to rise linearly with the surrounding O # tension, up to a threshold level (30-100 µM O # , depending on the species), above which consumption is arrested due to the formation of reactive oxygen species (Paget et al, 1993b ;Biagini et al, 1997 ;Lloyd et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these organisms lack mitochondria or detectable cytochromes (Brugerolle, 1974 ;Paget et al, 1993b ;Biagini et al, 1997) (and hence oxidative phosphorylation), but do, however, have high affinities for O # , comparable to those of aerobic protozoa (Paget et al, 1993b ;Biagini et al, 1997). The consumption of O # has IP: 54.191.190.102 On: Fri, 11 May 2018 00:32:14 G. A. BIAGINI and OTHERS been shown to rise linearly with the surrounding O # tension, up to a threshold level (30-100 µM O # , depending on the species), above which consumption is arrested due to the formation of reactive oxygen species (Paget et al, 1993b ;Biagini et al, 1997 ;Lloyd et al, 2000). The oxygen consumption has been attributed to the activity of NAD(P)H oxidase, and it has been postulated that the subsequent change in the redox state of the NAD(P)H pools affects the relative rates of production of end-products (Brown et al, 1998 ;Paget et al, 1993a ;Biagini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%